A negative electrode sheet and its preparation method and application
By using high-active strength materials in the Overhang area of the negative electrode sheet of the lithium-ion battery and using materials such as graphite or lithium titanate in the non-Overhang area, the problem of lithium evolution is solved, extending the cycle life of the battery and improving safety.
Patent Information
- Application Number
- CN202411954586.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The negative electrode sheets of existing lithium-ion batteries are prone to lithium extraction in the Overhang area, resulting in loss of active lithium and shortening of battery cycle life.
A negative electrode sheet was designed, and the active material layer in the Overhang area consists of materials with high activity strength (such as soft and hard carbon), and the active material layer in the non-Overhang area consists of materials such as graphite or lithium titanate. By adjusting the thickness and density of the material, the removal efficiency of lithium ions is improved.
It effectively reduces the risk of lithium excretion, extends the cycle life of the battery cell, and improves the safety of the battery cell.
Smart Images

Figure CN119764338A_ABST
Abstract
Description
Technical Field
[0001] This patent relates to the field of materials, mainly to a negative electrode sheet and its preparation method and application. Background Art
[0002] Lithium-ion batteries are widely used as energy storage devices for portable applications such as mobile phones, laptops, and digital electronics due to their high energy and power density, low memory effect, and environmental friendliness. With the rapid development of technology, the application of lithium-ion batteries has expanded to large-scale energy storage and electric vehicles to replace traditional energy sources such as fossil fuels.
[0003] During the operation of lithium-ion batteries, if the negative electrode has no position to accept lithium ions, lithium deposition will occur on the negative electrode surface. Therefore, in the initial design stage, the negative electrode sheet will exceed the positive electrode sheet by a certain length (overhang) in both length and width directions, and the area relative to the positive electrode is larger. This design has practical benefits because it can minimize the risk of lithium deposition on the edge of the negative electrode sheet during charging.
[0004] In the battery, in order to prevent lithium deposition at the edge of the negative electrode, the length and width of the coating of the negative electrode should be larger than that of the coating of the positive electrode. The Overhang area is also a normal graphite coating. During the charging process, the end is generally constant voltage charging. During this process, the lithium ions in the graphite in the negative electrode area corresponding to the positive electrode will diffuse to the Overhang area. In the subsequent discharge process, since there is no corresponding positive electrode in the Overhang area, the ions in the Overhang area need to diffuse into the normal graphite area first, and then enter the positive electrode. The graphite diffusion rate is low, and the lithium ions in this area are not completely released. As the number of charge and discharge times increases, the accumulated ion concentration in the Overhang area is higher, and lithium deposition and other phenomena are prone to occur, resulting in loss of active lithium.
[0005] CN117558872A discloses laser etching holes in the overhang area to avoid the reversible capacity loss caused by incomplete discharge. However, the preparation process of this technology is not yet mature, the hole-punching operation is relatively cumbersome, and it is not suitable for industrial production.
[0006] There are also ways in the prior art to solve the lithium deposition phenomenon by reducing the Overhang area. Reducing the width of the Overhang area means reducing the area of the Overhang area, thereby reducing the enrichment of active lithium during the charge and discharge process, thereby slowing down the lithium deposition phenomenon. The current mass production coating equipment generally controls the Overhang width at 1mm~10mm. If the width of the Overhang area is further reduced to the μm level, it is necessary to develop more precise equipment to increase production and efficiency. The entire industry has an increasing demand for coating width, especially for large-scale power storage batteries, where the coating width is at the m level. If the control is further improved with higher requirements for accuracy in the width direction, it will pose a great challenge to equipment manufacturers and equipment costs, so the feasibility of mass production is extremely low. Summary of the invention
[0007] In order to solve the problem of lithium deposition in the overhang area in the prior art, the present invention provides a negative electrode sheet and a preparation method and application thereof. The negative electrode sheet of the present invention can achieve one or more of the effects of reducing the risk of lithium deposition, extending the cycle life of the battery cell, and improving the safety of the battery cell.
[0008] The present invention provides a negative electrode sheet, wherein the overhang region of the negative electrode sheet has a higher activity intensity than the non-overhang region.
[0009] In the present invention, the negative electrode sheet includes an overhang area and a non-overhang area; the overhang area refers to the area where the negative electrode sheet and the positive electrode sheet do not overlap, and the non-overhang area refers to the area where the negative electrode sheet and the positive electrode sheet overlap.
[0010] In one embodiment of the present invention, the negative electrode sheet includes a current collector and an active material layer disposed on the surface of the current collector.
[0011] In one embodiment of the present invention, the current collector may be copper foil.
[0012] In one embodiment of the present invention, the width of the Overhang area is 1-10 mm, for example, 3 mm.
[0013] In one embodiment of the present invention, the width of the non-overhang area is 160-250 mm, for example, 198 mm.
[0014] In one embodiment of the present invention, the thickness of the active material layer in the Overhang region may be 10-50 μm, for example, 50 μm, and the thickness of the active material layer does not include the thickness of the current collector.
[0015] In one embodiment of the present invention, the thickness of the active material layer in the non-Overhang region may be 80 μm to 230 μm, for example, 120 μm, and the thickness of the active material layer does not include the thickness of the current collector.
[0016] In one embodiment of the present invention, the electrode surface density of the active material layer in the Overhang region is 2-6 mg / cm 2 , for example 4mg / cm 2 .
[0017] In one embodiment of the present invention, the electrode surface density of the active material layer in the non-overhang area is 10-15 mg / cm 2 , for example 10mg / cm 2 .
[0018] In one embodiment of the present invention, the compaction density of the active material layer may be a conventional compaction density of this type of negative electrode sheet in the art, for example, 1.0-1.8 g / cm 3 , further example 1.65~1.70g / cm 3 ; The active material layer includes an active material layer in the Overhang area and an active material layer in the non-Overhang area.
[0019] In one embodiment of the present invention, the active material in the Overhang region has a higher activity intensity than the active material in the non-Overhang region, which is specifically manifested in that the RATE-D value of the active material is higher; for example, the ratio of the RATE-D value of the active material in the Overhang region to the active material in the non-Overhang region is 1.5-10, and further examples are 6.38, 4.73, 3.22, 2.39, and 9.03.
[0020] In one embodiment of the present invention, the active material in the Overhang region and the active material in the non-Overhang region are one of graphite, soft carbon, hard carbon and lithium titanate.
[0021] In one embodiment of the present invention, the active material layer in the Overhang region includes an active material 1, a conductive agent, and a binder; the active material 1 is graphite.
[0022] In one embodiment of the present invention, the active material layer in the non-Overhang region includes an active material 2, a conductive agent, and a binder; the active material 2 may be at least one of soft carbon, hard carbon, and lithium titanate.
[0023] In one embodiment of the present invention, the conductive agent of the negative electrode sheet may be a conventional conductive agent for negative electrode sheets of this type in the art, such as SP, and further such as Super-P purchased from Yiruishi.
[0024] In one embodiment of the present invention, the binder of the negative electrode sheet may be a conventional binder for this type of negative electrode sheet in the art, such as at least one of sodium carboxymethyl cellulose, sodium alginate, styrene-butadiene rubber and acrylic binders, such as sodium carboxymethyl cellulose and styrene-butadiene rubber, and further such as MAC500 sodium carboxymethyl cellulose purchased from Nippon Paper and SN307 styrene-butadiene rubber purchased from A&L.
[0025] In one embodiment of the present invention, the active material layer in the non-Overhang area is composed of active material 1, a binder, and a conductive agent; the active material 1 is graphite; the active material layer in the Overhang area is composed of active material 2, a binder, and a conductive agent; the active material 2 is at least one of soft carbon, hard carbon, and lithium titanate.
[0026] In one embodiment of the present invention, in the Overhang region, the mass ratio of the active material 1, the binder, and the conductive agent may be a conventional mass ratio in this type of negative electrode sheet in the art, for example, 92.5~96:2.5~9:0.5~2.5.
[0027] In one embodiment of the present invention, in the non-Overhang region, the mass ratio of the active material 2, the binder, and the conductive agent may be a conventional mass ratio in this type of negative electrode sheet in the art, for example, 92.5~96:2.5~9:0.5~2.5.
[0028] In one embodiment of the present invention, the mass ratio of sodium carboxymethyl cellulose to styrene-butadiene rubber may be 1-3:1.5-6; preferably 2:3; more preferably 1.4:1.8.
[0029] In one embodiment of the present invention, in the active material layer in the Overhang region, the mass ratio of the active material 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and the conductive agent is 92.5-96:1-3:1.5-6:0.5-2.5.
[0030] In one embodiment of the present invention, in the active material layer in the non-Overhang region, the mass ratio of the active material 2, sodium carboxymethyl cellulose, styrene-butadiene rubber and the conductive agent is 92.5~96:1~3:1.5~6:0.5~2.5.
[0031] In one embodiment of the present invention, the active material layer in the Overhang region is composed of soft carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P;
[0032] The active material layer in the non-Overhang area is composed of graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P;
[0033] In the active material layer of the Overhang region, the mass ratio of soft carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0;
[0034] In the active material layer of the non-Overhang region, the mass ratio of graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0;
[0035] The sodium carboxymethyl cellulose is MAC500 sodium carboxymethyl cellulose purchased from Nippon Paper;
[0036] The styrene butadiene rubber is SN307 styrene butadiene rubber purchased from A&L;
[0037] The conductive agent is Super-P conductive carbon black purchased from Yiruishi;
[0038] The width of the Overhang area is 3 mm;
[0039] The width of the non-overhang area is 198 mm;
[0040] The thickness of the active material layer in the Overhang region is 50 μm;
[0041] The thickness of the active material layer in the non-Overhang area is 120 μm;
[0042] The current collector of the negative electrode sheet is copper foil;
[0043] The electrode surface density of the active material layer in the Overhang region is 4 mg / cm 2 ;
[0044] The electrode surface density of the active material layer in the non-overhang area is 10 mg / cm 2 ;
[0045] The compaction density of the active material layer is 1.65-1.70 g / cm 3 ;
[0046] The ratio of the soft carbon to the graphite RATE-D is 6.38.
[0047] In one embodiment of the present invention, the active material layer in the Overhang region is composed of hard carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P;
[0048] The active material layer in the non-Overhang area is composed of graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P;
[0049] In the active material layer of the Overhang region, the mass ratio of hard carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0;
[0050] In the active material layer of the non-Overhang region, the mass ratio of graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0;
[0051] The sodium carboxymethyl cellulose is MAC500 sodium carboxymethyl cellulose purchased from Nippon Paper;
[0052] The styrene butadiene rubber is SN307 styrene butadiene rubber purchased from A&L;
[0053] The conductive agent is Super-P conductive carbon black purchased from Yiruishi;
[0054] The width of the Overhang area is 3 mm;
[0055] The width of the non-overhang area is 198 mm;
[0056] The thickness of the active material layer in the Overhang region is 50 μm;
[0057] The thickness of the active material layer in the non-Overhang area is 120 μm;
[0058] The current collector of the negative electrode sheet is copper foil;
[0059] The electrode surface density of the active material layer in the Overhang region is 4 mg / cm 2 ;
[0060] The electrode surface density of the active material layer in the non-overhang area is 10 mg / cm 2 ;
[0061] The compaction density of the active material layer is 1.65-1.70 g / cm 3 ;
[0062] The RATE-D ratio of the hard carbon to the graphite is 4.73.
[0063] In one embodiment of the present invention, the active material layer in the Overhang region is composed of lithium titanate, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P;
[0064] The active material layer in the non-Overhang area is composed of graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P;
[0065] In the active material layer of the Overhang region, the mass ratio of hard carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0;
[0066] In the active material layer of the non-Overhang region, the mass ratio of lithium titanate, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0;
[0067] The sodium carboxymethyl cellulose is MAC500 sodium carboxymethyl cellulose purchased from Nippon Paper;
[0068] The styrene butadiene rubber is SN307 styrene butadiene rubber purchased from A&L;
[0069] The conductive agent is Super-P conductive carbon black purchased from Yiruishi;
[0070] The width of the Overhang area is 3 mm;
[0071] The width of the non-overhang area is 198 mm;
[0072] The thickness of the active material layer in the Overhang region is 50 μm;
[0073] The thickness of the active material layer in the non-Overhang area is 120 μm;
[0074] The current collector of the negative electrode sheet is copper foil;
[0075] The electrode surface density of the active material layer in the Overhang region is 4 mg / cm 2 ;
[0076] The electrode surface density of the active material layer in the non-overhang area is 10 mg / cm 2 ;
[0077] The compaction density of the active material layer is 1.65-1.70 g / cm 3 ;
[0078] The ratio of the lithium titanate to the graphite RATE-D is 9.03.
[0079] The second object of the present invention is to provide a method for preparing the negative electrode sheet, comprising the following steps:
[0080] S1: Active material 1, a binder, a conductive agent and a solvent are mixed to obtain slurry 1; active material 2, a binder, a conductive agent and a solvent are mixed to obtain slurry 2;
[0081] S2: coating the obtained slurry 1 on the non-overhang surface of the current collector; coating the obtained slurry 2 on the overhang surface of the current collector; drying, rolling, and cutting to obtain a negative electrode sheet including an overhang area and a non-overhang area;
[0082] The definitions of active material 1, active material 2, binder and conductive agent are the same as those in the previous embodiment.
[0083] In one embodiment of the present invention, the solvent may be deionized water.
[0084] In one embodiment of the present invention, the solid content of the slurry 1 may be 40%-60%, for example, 54%. The solid content refers to the mass ratio of the active material 1, the binder, the conductive agent and the slurry 1.
[0085] In one embodiment of the present invention, the solid content of the slurry 2 may be 40%-60%, for example, 54%. The solid content refers to the mass ratio of the active material 2, the binder, the conductive agent and the slurry 2.
[0086] In one embodiment of the present invention, the viscosity of the slurry 1 and the slurry 2 may be a conventional viscosity of such slurries in the art, such as 2000 mPa.s-6000 mPa.s, and for example 3800 mPa.s.
[0087] In one embodiment of the present invention, the slurry 1 has a solid content of 54% and a viscosity of 3800 mPa.s.
[0088] In one embodiment of the present invention, the solid content of the slurry 2 is 54% and the viscosity is 3800 mPa.s.
[0089] In one embodiment of the present invention, the drying temperature may be a conventional temperature in the preparation of negative electrode sheets of this type in the art, such as 80-140° C., and further such as 95° C.
[0090] A negative electrode sheet is prepared by the above preparation method.
[0091] The third object of the present invention is to provide a lithium-ion battery comprising the above-mentioned negative electrode sheet.
[0092] In one embodiment of the present invention, the cell structure of the lithium-ion battery is formed by stacking or winding a separator-negative electrode sheet-separator-positive electrode unit in sequence; the outermost layer of the cell structure is the separator.
[0093] In one embodiment of the present invention, the CB value of the lithium-ion battery is 1.0-1.1.
[0094] In one embodiment of the present invention, the electrolyte of the lithium-ion battery is a mixture of 1M LiPF6, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a mass ratio of 1:1:1.
[0095] In one embodiment of the present invention, the separator of the lithium-ion battery is a PE (polyethylene) / PP (polypropylene) / PE (polyethylene) composite film.
[0096] The above technical solution of the present invention has the following advantages compared with the prior art:
[0097] The lithium battery negative electrode provided by the present invention is obtained by coating the overhang area with materials such as soft and hard carbon with high capacity or strong fast charging ability, and coating the non-overhang area with graphite material. This type of material has better rate performance than graphite, and lithium ions can be quickly released into the graphite, thereby improving the utilization rate of active lithium and reducing the risk of edge lithium precipitation.
[0098] 2. Use non-carbon materials as coating slurry. For example, the median voltage of lithium titanate is higher than that of graphite, and it will not reach the lithium plating potential, which is safer. BRIEF DESCRIPTION OF THE DRAWINGS
[0099] Figure 1 Schematic diagram of the structure of the negative electrode sheet of this application
[0100] Figure 2 The appearance of the soft pack battery in Example 1
[0101] Figure 3 The appearance of the soft pack battery in Example 2
[0102] Figure 4 The appearance of the soft pack battery in Example 3
[0103] Figure 5 The appearance of the soft pack battery in Example 4
[0104] Figure 6 Appearance of the soft pack battery in Example 5
[0105] Figure 7 The appearance of the soft pack battery of comparative example 1
[0106] Figure 8 The appearance of the soft pack battery of comparative example 2 DETAILED DESCRIPTION
[0107] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0108] Figure 1 This is a schematic diagram of the structure of the negative electrode sheet (Examples 1-5) of the present application, wherein Figure 1 The mark 1 is the positive electrode, Figure 1 The mark 2 is the diaphragm, Figure 1 The mark 3 is the non-overhang area active material layer (slurry 1), Figure 1 The mark 4 is the active material layer in the Overhang region (slurry 2), Figure 1 The mark 5 is the current collector (copper foil).
[0109] Example 1
[0110] 1. Graphite 1, sodium carboxymethyl cellulose, styrene butadiene rubber and SP (conductive carbon black) were dispersed in deionized water solvent at a mass ratio of 95.8:1.4:1.8:1.0 and mixed evenly. The solid content was 54% and the viscosity was 3800 mPa.s to obtain slurry 1. Soft carbon (soft carbon 1), sodium carboxymethyl cellulose, styrene butadiene rubber and SP were also dispersed in deionized water solvent at a mass ratio of 92.5:2.0:3.0:2.5 to obtain slurry 2.
[0111] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 13 mg / cm 2 (Slurry 1 is applied to the Overhang area to form an active material layer with a single-sided surface density of 4 mg / cm 2 , the width is controlled at 3mm; slurry 2 is applied to the non-overhang area to form an active material layer, with a single-sided surface density of 10mg / cm 2 , width controlled at 198mm), dried at 95°C, and roller pressed (compacted density 1.65~1.70g / cm 3 , the thickness of the active material layer in the Overhang area is controlled at 50μm, and the thickness of the active material layer in the non-Overhang area is controlled at 120μm, and this thickness does not count the thickness of the current collector) and slitting to obtain a negative electrode sheet including the Overhang area and the non-Overhang area. The coating method can be an extrusion coater with a compaction density of 1.65~1.70g / cm 3The principle is similar to that of positive electrode alumina coating.
[0112] 3. Assemble the battery with the positive electrode and test it. Figure 2 Shown
[0113] The cycle capacity retention rate and battery cell appearance were evaluated. After 1000 cycles, the capacity retention rate was 90.1%, the cycle trend was stable, the cycle data was shown in Table 2, and the battery appearance was good.
[0114] Example 2
[0115] 1. Graphite 1, sodium carboxymethyl cellulose, styrene butadiene rubber and SP were dispersed in deionized water solvent in a mass ratio of 95.8:1.4:1.8:1.0, mixed evenly and adjusted the solid content to 54% and the viscosity to 3800 mPa.s to obtain slurry 1. Hard carbon 1, sodium carboxymethyl cellulose, styrene butadiene rubber and SP were also dispersed in deionized water solvent in a mass ratio of 92.5:2.0:3.0:2.5 to obtain slurry 2.
[0116] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 13 mg / cm 2 (Slurry 1 is applied to the Overhang area to form an active material layer with a single-sided surface density of 4 mg / cm 2 , the width is controlled at 3mm; slurry 2 is applied to the non-overhang area to form an active material layer, with a single-sided surface density of 10mg / cm 2 , width controlled at 198mm), dried at 95°C, and roller pressed (compacted density 1.65~1.70g / cm 3 , the thickness of the active material layer in the Overhang area is controlled at 50μm, and the thickness of the active material layer in the non-Overhang area is controlled at 120μm, and this thickness does not count the thickness of the current collector) and slitting to obtain a negative electrode sheet including the Overhang area and the non-Overhang area. The coating method can be an extrusion coater (compacted density 1.65~1.70g / cm 3 ), the principle refers to the positive electrode alumina coating coating.
[0117] 3. Assemble the battery with the positive electrode (same as in Example 1) and test it. Figure 3 shown.
[0118] After 1000 cycles, it was found that there was no lithium deposition on the edge of the Overhang, and the cycle trend was better than the control. After 1000 cycles, the capacity retention rate was 90.6%, the cycle trend was stable, and the cycle data was shown in Table 2. The battery appearance was good.
[0119] Example 3
[0120] 1. Disperse graphite 2, sodium carboxymethyl cellulose, styrene butadiene rubber and SP in solvent deionized water in a mass ratio of 95.8:1.4:1.8:1.0, mix well and adjust the solid content to 54% and the viscosity to 3800 mPa.s to obtain slurry 1. Disperse soft carbon 1, sodium carboxymethyl cellulose, styrene butadiene rubber and SP in solvent deionized water in a mass ratio of 92.5:2.0:3.0:2.5 to obtain slurry 2.
[0121] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 13 mg / cm 2 (Slurry 1 is applied to the Overhang area to form an active material layer with a single-sided surface density of 4 mg / cm 2 , the width is controlled at 3mm; slurry 2 is applied to the non-overhang area to form an active material layer, with a single-sided surface density of 10mg / cm 2 , width controlled at 198mm), dried at 95°C, and roller pressed (compacted density 1.65~1.70g / cm 3 , the thickness of the active material layer in the Overhang area is controlled at 50μm, and the thickness of the active material layer in the non-Overhang area is controlled at 120μm, and this thickness does not count the thickness of the current collector) and slitting to obtain a negative electrode sheet including the Overhang area and the non-Overhang area. The coating method can be an extrusion coater with a compaction density of 1.65~1.70g / cm 3 The principle is similar to that of positive electrode alumina coating.
[0122] 3. Assemble the battery with the positive electrode (same as in Example 1) and test it. Figure 4 shown.
[0123] After 1000 cycles, it was found that there was no lithium deposition on the edge of the Overhang, and the cycle trend was better than the control. After 1000 cycles, the capacity retention rate was 94.6%, the cycle trend was stable, and the battery appearance was good.
[0124] Example 4
[0125] 1. Disperse graphite 2, sodium carboxymethyl cellulose, styrene butadiene rubber and SP in a solvent deionized water according to a mass ratio of 95.8:1.4:1.8:1.0, mix well and adjust the solid content to 54% and the viscosity to 3800 mPa.s to obtain slurry 1. Disperse hard carbon 1, sodium carboxymethyl cellulose, styrene butadiene rubber and SP in a solvent deionized water according to a mass ratio of 92.5:2.0:3.0:2.5 to obtain slurry 2.
[0126] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 13 mg / cm2 (Slurry 1 is applied to the Overhang area to form an active material layer with a single-sided surface density of 4 mg / cm 2 , the width is controlled at 3mm; slurry 2 is applied to the non-overhang area to form an active material layer, with a single-sided surface density of 10mg / cm 2 , width controlled at 198mm), dried at 95°C, and roller pressed (compacted density 1.65~1.70g / cm 3 , the thickness of the active material layer in the Overhang area is controlled at 50μm, and the thickness of the active material layer in the non-Overhang area is controlled at 120μm, and this thickness does not count the thickness of the current collector) and slitting to obtain a negative electrode sheet including the Overhang area and the non-Overhang area. The coating method can be an extrusion coater with a compaction density of 1.65~1.70g / cm 3 The principle is similar to that of positive electrode alumina coating.
[0127] 3. Assemble the battery with the positive electrode and test it (same as in Example 1). Figure 5 shown.
[0128] After 1000 cycles, it was found that there was no lithium deposition on the edge of the Overhang, and the cycle trend was better than the control. After 1000 cycles, the capacity retention rate was 92.5%, the cycle trend was stable, and the battery appearance was good.
[0129] Example 5
[0130] 1. Graphite 2, sodium carboxymethyl cellulose, styrene butadiene rubber and SP were dispersed in deionized water solvent in a mass ratio of 95.8:1.4:1.8:1.0, mixed evenly and adjusted the solid content to 54% and the viscosity to 3800 mPa.s to obtain slurry 1. Lithium titanate (LTO1), sodium carboxymethyl cellulose, styrene butadiene rubber and SP were also dispersed in deionized water solvent in a mass ratio of 92.5:2.0:3.0:2.5 to obtain slurry 2.
[0131] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 13 mg / cm 2 (Slurry 1 is applied to the Overhang area to form an active material layer with a single-sided surface density of 4 mg / cm 2 , the width is controlled at 3mm; slurry 2 is applied to the non-overhang area to form an active material layer, with a single-sided surface density of 10mg / cm 2 , width controlled at 198mm), dried at 95°C, and roller pressed (compacted density 1.65~1.70g / cm 3, the thickness of the active material layer in the Overhang area is controlled at 50μm, and the thickness of the active material layer in the non-Overhang area is controlled at 120μm, and the thickness does not count the thickness of the current collector) and slitting to obtain a negative electrode sheet including the Overhang area and the non-Overhang area. The coating method can be an extrusion coater, (compacted density 1.65~1.70g / cm 3 ) The principle refers to the positive electrode alumina coating coating.
[0132] 3. Assemble the battery with the positive electrode and test it (same as in Example 1). Figure 6 shown.
[0133] After 1000 cycles, it was found that there was no lithium deposition on the edge of the Overhang, and the cycle trend was better than the control. After 1000 cycles, the capacity retention rate was 93.1%, the cycle trend was stable, and the battery appearance was good.
[0134] Comparative Example 1
[0135] 1. Graphite 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and SP were dispersed in deionized water as a solvent in a mass ratio of 95.8:1.4:1.8:1.0, mixed evenly and adjusted to a solid content of 54% and a viscosity of 3800 mPa.s to obtain slurry 1.
[0136] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 10 mg / cm 2 , and dried at 95°C, and rolled and cut to obtain a negative electrode sheet including an Overhang area and a non-Overhang area. The coating method can be an extrusion coater, and the principle refers to the positive electrode alumina coating coating.
[0137] 3. Assemble with the positive electrode sheet into a battery and test. (Same as Example 1) Figure 7 shown.
[0138] Comparative Example 2
[0139] 1. Graphite 2, sodium carboxymethyl cellulose, styrene-butadiene rubber and SP were dispersed in deionized water as a solvent in a mass ratio of 95.8:1.4:1.8:1.0, mixed evenly and adjusted to a solid content of 54% and a viscosity of 3800 mPa.s to obtain slurry 1.
[0140] 2. The slurry obtained in step 1 is evenly coated on the copper foil with a coating surface density of 10 mg / cm 2 , and dried at 95°C, and rolled and cut to obtain a negative electrode sheet including an Overhang area and a non-Overhang area. The coating method can be an extrusion coater, and the principle refers to the positive electrode alumina coating coating.
[0141] 3. Assemble the battery with the positive electrode and test it (same as in Example 1). Figure 8 shown.
[0142] Test of various material parameters (using button battery test)
[0143] Lithium metal was used as the counter electrode, the electrolyte was a mixture of 1M LiPF6 in ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a mass ratio of 1:1:1, the separator was a PE / PP / PE composite film, and the button cell was assembled. The material parameters described in Table 1 were obtained by testing.
[0144] Table 1
[0145]
[0146] The uncoated graphite 1, coated graphite 2, hard carbon 1, soft carbon 1, and LTO1 were tested for particle size, tap compaction, BET (specific surface area), etc. The ID / IG of the materials was tested using a Qontor (Renishaw, UK) Raman spectrometer for surface defect and activity analysis, and the rate lithium insertion performance of the materials was tested using a CR-2430 button half-cell. In the Raman test, the higher the peak intensity ratio of the D peak (characteristic peak of disordered carbon) to the G peak (characteristic peak of disordered carbon) of the Raman spectrum of the carbon material, the higher the degree of disorder on the material surface, and the higher the rate lithium insertion ratio of the button cell, the higher the lithium insertion rate of the material and the higher the corresponding surface activity.
[0147] The preparation method of the CR-2430 button half-cell used for the rate performance of the material is as follows: the graphite negative electrode materials made of graphite 1, graphite 2, hard carbon 1, soft carbon 1, and LTO1 are mixed with carboxymethyl cellulose (MAC500 sodium carboxymethyl cellulose, purchased from Nippon Paper), styrene butadiene rubber (SN307 styrene butadiene rubber, purchased from A&L), and conductive agent (Super-P, purchased from Yiruishi) in a mass ratio of 92.5:3.0:2.0:2.5; coated on copper foil, vacuum dried and used as the negative electrode, and the obtained negative electrode surface density is ~10mg / cm 2 ; Compacted density 1.0~1.60g / cm 3 . (This compaction is the compaction density of the withholding test)
[0148] Negative electrode lithium plating effect test (intuitively judge based on the degree of cell deformation, disassemble the battery, and analyze the battery cycle performance)
[0149] (The positive electrode NCM811 (S85E, Rongbai), PVDF (5130, Solvay), SP (Super-Li) were dispersed in the solvent NMP according to the mass ratio of 97.3:1.2:1.5, mixed evenly and adjusted the solid content to 74%, the viscosity to 3800mPa.s, to obtain the positive electrode slurry, sprayed on the positive electrode current collector, the double-sided surface density was 42.5 mg / cm2, and dried at 130℃ to obtain the positive electrode sheet, and the roller compaction density was 3.5 g / cm 3 ;
[0150] The separator is a 9 μm PE / PP / PE composite film, which is wound and assembled into a battery. The electrolyte used is a mixture of 1M LiPF6 in ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) with a mass ratio of 1:1:1, in which 1% of vinylene carbonate (VC) is added. The injection coefficient is 5g / Ah, and a soft-pack battery with a nominal capacity of 2.8Ah is prepared. (Formation process: 0.2C charging to 4.3V, constant voltage 4.3V cut-off current 0.05C, standing for 30min , 0.2C discharge to 2.5V, stand for 30min, cut off with current 0.01C), and then carry out 25℃ cycle test, cycle test steps: discharge step: discharge step: 1C discharge to 2.5V, stand for 30min, cut off with current 0.01C; charging step: 1C charge to 4.3V, constant voltage 4.3V cut off current 0.05C, stand for 30min.
[0151] (1) Test method for reversible gram capacity: Discharge step: 0.1C discharge to 5mV, constant voltage 5mV, cut off at current 0.01C, the obtained capacity is the discharge capacity of the negative electrode material; Charge step: 0.1C charge to 2V, the obtained capacity is the charge capacity of the negative electrode material, i.e. the reversible capacity.
[0152] (2) Test method for first efficiency: The test method is the same as the reversible gram capacity test method. The first efficiency is the ratio of the first charge capacity to the first discharge capacity.
[0153] (3) Rate test method: Discharge step: 0.1C discharge to 5mV, constant voltage 5mV, cut off at current 0.01C; Charge step: 0.1C charge to 2V; Discharge at currents of 0.2C, 0.5C, 1.0C, 2.0C, and 3.0C (charge is always at 0.1C) for 5 cycles, and the ratio of the capacity of the constant current discharge section to the total discharge capacity of 0.2C is selected for comparison.
[0154] After 600 cycles, the capacity retention rate decays rapidly, and after 1000 cycles, the capacity retention rate is 76.7%, and the cycle failure is obvious. The cycle data. The lithium deposition at the edge of the battery in Comparative Example 1 leads to lithium deposition deformation, such as Figure 7 As shown, Figure 7The upper part of the mark 1 near the pole ear position has a bulging deformation caused by lithium deposition. The edge of the battery in comparative example 2 has lithium deposition causing lithium deposition deformation. Figure 8 As shown, Figure 8 The bulging deformation caused by lithium deposition near the pole ear at the upper part of the marked 1 position is the main reason for the abnormal cycle.
[0155] After 1000 cycles, lithium deposition was found on the overhang edge. After 500 cycles, the capacity retention rate decayed rapidly, and after 1000 cycles, the capacity retention rate was 71.9%, indicating obvious cycle failure. The cycle data is shown in Table 2.
[0156] Table 2
[0157]
[0158] Lithium deposition at the edge of the battery causes deformation and combined Figure 2-8 The degree of deformation of the battery cells in the battery is compared. The battery appearance of Examples 1-5 is good, while that of Comparative Examples 1-2 ( Figure 7 and Figure 8 ) The bulging deformation caused by lithium deposition near the upper ear is the main cause of the abnormal cycle.
Claims
1. A negative electrode sheet, wherein the overhang area of the negative electrode sheet has a higher activity intensity than the non-overhang area.
2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode sheet comprises a current collector and an active material layer arranged on the surface of the current collector.
3. The negative electrode sheet according to claim 2, characterized in that: It meets one or more of the following conditions: (1) The current collector is copper foil; (2) The active material in the Overhang region has a higher activity intensity than the active material in the non-Overhang region, and the higher activity intensity means that the active material in the Overhang region has a higher RATE-D value than the active material in the non-Overhang region; for example, the ratio of the RATE-D value of the active material in the Overhang region to the active material in the non-Overhang region is 1.5-10; further examples are 6.38, 4.73, 3.22, 2.39, 9.03; (3) The active material in the Overhang region and the active material in the non-Overhang region are one of graphite, soft carbon, hard carbon, and lithium titanate; (4) The active material layer in the Overhang region includes an active material 1, a conductive agent, and a binder; the active material 1 is graphite; (5) The active material layer in the non-Overhang region includes an active material 2, a conductive agent, and a binder; the active material 2 is at least one of soft carbon, hard carbon, and lithium titanate; (6) The thickness of the active material layer in the Overhang region is 10-50 μm, for example 50 μm; (7) The thickness of the active material layer in the non-overhang area is 80 μm to 230 μm, for example, 120 μm; (8) The width of the Overhang area is 1-10 mm, for example 3 mm; (9) The width of the non-overhang area is 160-250 mm, for example, 198 mm; (10) The electrode surface density of the active material layer in the overhang region is 2-6 mg / cm 2 , for example 4mg / cm 2 (11) The electrode surface density of the active material layer in the non-overhang area is 5-15 mg / cm 2 , for example 10mg / cm 2 ; (12) The compaction density of the active material layer is 1.0-1.8 g / cm 3 , for example 1.65~1.70g / cm 3 ; Preferably, it satisfies one or more of the following conditions: (1) The conductive agent is SP, such as Super-P purchased from Yiruishi; (2) The binder is at least one of sodium carboxymethyl cellulose, sodium alginate, styrene-butadiene rubber and acrylic binders, such as sodium carboxymethyl cellulose and styrene-butadiene rubber, and further such as MAC500 sodium carboxymethyl cellulose purchased from Nippon Paper and SN307 styrene-butadiene rubber purchased from A&L.
4. The negative electrode sheet according to claim 3, characterized in that: The active material layer in the non-Overhang area is composed of active material 1, a binder, and a conductive agent; the active material 1 is graphite; the active material layer in the Overhang area is composed of active material 2, a binder, and a conductive agent; the active material 2 is at least one of soft carbon, hard carbon, and lithium titanate.
5. The negative electrode sheet according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In the Overhang region, the mass ratio of the active material 1, the binder, and the conductive agent is 92.5-96:2.5-9:0.5-2.5; (2) In the non-overhang area, the mass ratio of the active material 2, the binder, and the conductive agent is 92.5-96: 2.5-9: 0.5-2.5; (3) The mass ratio of sodium carboxymethyl cellulose to styrene-butadiene rubber is 1-3:1.5-6; preferably 2:3; more preferably 1.4:1.8; Preferably, it satisfies one or more of the following conditions: (1) In the active material layer of the Overhang region, the mass ratio of the active material 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and conductive agent is 92.5-96:1-3:1.5-6:0.5-2.5; (2) In the active material layer in the non-overhang area, the mass ratio of the active material 2, sodium carboxymethyl cellulose, styrene-butadiene rubber and conductive agent is 92.5-96:1-3:1.5-6:0.5-2.
5.
6. The negative electrode sheet according to claim 5, characterized in that: It meets at least one of the following conditions: (1) The active material layer in the Overhang region is composed of soft carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P; the ratio of the soft carbon to the graphite RATE-D is 6.38; Or, the active material layer in the Overhang region is composed of hard carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P; the ratio of the hard carbon to the graphite RATE-D is 4.73; Or, the active material layer in the Overhang region is composed of lithium titanate, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P; the ratio of lithium titanate to graphite RATE-D is 9.03; (2) The active material layer in the non-Overhang region is composed of graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P; (3) In the active material layer of the Overhang region, the mass ratio of active material 2, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0; (4) In the active material layer in the non-Overhang region, the mass ratio of active material 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super-P is 95.8:1.4:1.8:1.0; (5) The sodium carboxymethyl cellulose is MAC500 sodium carboxymethyl cellulose purchased from Nippon Paper; (6) The styrene butadiene rubber is SN307 styrene butadiene rubber purchased from A&L; (7) The conductive agent is Super-P conductive carbon black purchased from Yiruishi; (8) The width of the active material layer in the Overhang area is 3 mm; (9) The width of the active material layer in the non-overhang area is 198 mm; (10) The thickness of the active material layer in the Overhang region is 50 μm; (11) The thickness of the active material layer in the non-Overhang region is 120 μm; (12) The current collector of the negative electrode sheet is copper foil; (13) The electrode surface density of the active material layer in the overhang region is 4 mg / cm 2 ; (14) The electrode surface density of the active material layer in the non-overhang area is 10 mg / cm 2 ; (15) The compacted density of the active material layer is 1.65-1.70 g / cm 3 .
7. A method for preparing a negative electrode sheet, comprising the following steps: S1: Active material 1, a binder, a conductive agent and a solvent are mixed to obtain slurry 1; active material 2, a binder, a conductive agent and a solvent are mixed to obtain slurry 2; S2: coating the obtained slurry 1 on the non-overhang surface of the current collector; coating the obtained slurry 2 on the overhang surface of the current collector; drying, rolling, and cutting to obtain a negative electrode sheet including an overhang area and a non-overhang area; The definitions of active material 1, active material 2, binder and conductive agent are as shown in any one of claims 1-6.
8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: It meets one or more of the following conditions: (1) The solvent is deionized water; (2) The solid content of the slurry 1 is 40%-60%, for example 54%, and the solid content refers to the mass ratio of the active material 1, the binder, the conductive agent to the slurry 1; (3) The solid content of the slurry 2 is 40%-60%, for example 54%, and the solid content refers to the mass ratio of the active material 2, the binder, the conductive agent and the slurry 2; (4) The viscosity of the slurry 1 and the slurry 2 is 2000-6000 mPa.s, for example 3800 mPa.s; (5) The drying temperature is 80-140°C, for example 95°C; Preferably, it satisfies one or more of the following conditions: (1) The solid content of the slurry 1 is 54% and the viscosity is 3800 mPa.s; (2) The solid content of the slurry 2 is 54% and the viscosity is 3800 mPa.s.
9. A negative electrode sheet, prepared by the preparation method according to any one of claims 7 to 8.
10. A lithium ion battery comprising the negative electrode sheet according to any one of claims 1 to 6; Preferably, it satisfies one or more of the following conditions: (1) The cell structure of the lithium-ion battery is composed of a separator-negative electrode sheet-separator-positive electrode unit stacked or wound in sequence; the outermost layer of the cell structure is the separator; (2) The CB value of the lithium-ion battery is 1.0-1.1; (3) The electrolyte of the lithium-ion battery is a mixture of 1M LiPF6, ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1; (4) The separator of the lithium-ion battery is a polyethylene / polypropylene / polyethylene composite film.
Citation Information
Cited By
Preparation method of electrode plate, positive electrode plate, battery cell, solid-state battery and overhang slurry
CN120511270A